(untitled) (Africa Development, 2021)
Contents / Sommaire Introduction Lansana Keita................................1 Understanding the Political Economy of Contemporary Africa Samir Amin..................................15 Social Scientists’ Failure of Analytical Nerve: ‘Africa Rising’ From Above – Or Uprising From Below? Patrick Bond...............................37 Creolizing Political Identity and Social Scientific Method Jane Anna Gordon .......................65 Disciplinary Decadence and the Decolonization of Knowledge Lewis R. Gordon............................81 On the Problematic State of Economic ‘Science’ Lansana Keita..............................93 Thinking Political Emancipation and the Social Sciences in Africa: Some Critical Reflections Michael Neocosmos.....................125 The Concept of Innovation and the South African Nation Sanya Osha.........................159